Achieving virtues and perfections of the human potential of women in the Quran - Zohreh, Sadat Moosavi; Wan Ali, Wan Zailan Kamaruddin (2012)
Religious schools and communities have different opinions about the real perfection of women. Obviously, identifying the women's ultimate perfection has essential role to determine their fate and the fate of the human society. Among these schools, comprehensive Islamic law, which is originated from Divine revelation, has bestowed enormous status for women by paying great attention to women traits. According to the holy Quran, women are equal to men in terms of humanity. Certainly, there are a lot of wise genesis differences between men and women, but Divine revelations stresses that human truth and gender has no role in awarding guidance. The third longest Sura in the holy Quran is called "Al- Nnesa" that means women. Ten other Suras have also pointed to some women's affairs. Virtues of exemplar women are introduced by Quran as follows: the wife of Pharaoh, faith exemplar; mother of Moses (AS), exemplar of surrender to God, the wife of Moses (AS ), modesty exemplar; mother of Mary (SA), exemplar of honesty and sincerity, Mary (SA) exemplar of chastity and modesty ; wife of Zechariah (AS) exemplar of righteousness and obedience (SA) the wife of Job, a patient exemplar and the Queen of Saba, exemplar of surrender to God orders. In some Ahadith of the Prophet (SAW), mistresses of women in the paradise (and in other Ahadith, world) are four: Mary (mother of Jesus), Asia (wife of Pharaoh), Khadijah and Fatima. And the most perfect one is Fatima. These examples in the teaching of Islam themselves indicate possibility of growth and excellence in female personalities to the top of humanitarian virtues. The spiritual virtues of women in the Quran are divided into two groups: 1- individual virtues (piety and moral virtues) 2- social virtues. Women are able to achieve the best degree of sincerity, faith and piety as men. They are equal in religion (Islam), faithfulness, obedience ability, truthfulness, tolerance, fear of God and giving of alms, fasting, self-preservation, remembering God and finally in the extract of all virtues which is piety, (Al- AHzab 35). Moreover, Quran assigns social responsibilities to both men and women. In ignorant and superstitious communities in which women would only be considered as objects, Quran takes over a heavy responsibility such as promoting friendship and supervision, invitation to goodness and denial of badness, performing prayer and giving alms. The Prophet has got votes from women. This study is a library one and in deductive method. The main source is the holy Quran. Thus, men and women are equal in enjoyment of business and undertaking their duties and responsibilities and rewards. Physiological differences between men and women are essential to the survival of human life that gives rise to differences in some duties and rights. The purpose of this study is to describe women virtues in the Quran, which lead us to the conclusion that obtaining human virtues for men and women as a ratio is important because from the Quranic perspective both are equal in terms of humanity and the superiority of any being is determined by its virtuousness.